Effects of glycopyrrolate and atropine for oral secretions and perioperative hemodynamics in children undergoing tonsillectomy and adenoidectomy: a prospective, single-center, randomized, double-blind, controlled trial - Tao, Yi-Bin; Tang, Zi-Li; Lin, Zhong-Lan; Lei, Wei-Ping; Lu, Xin-Lei; Sun, Jian-Liang (Frontiers in Pharmacology, 2024)
Introduction Glycopyrrolate is commonly researched as a preoperative medication or in conjunction with cholinesterase inhibitors to counteract the lingering muscarinic effects of non-depolarizing muscarinic agents. However, studies have yielded inconsistent results regarding the superiority of glycopyrrolate over other anti-cholinergic drugs, such as atropine, particularly its effect on heart rate, blood pressure (BP), and glandular secretions. This study aimed to evaluate the differences in perioperative oral secretions, hemodynamics, and recovery quality with glycopyrrolate versus those with atropine before anesthesia induction in children undergoing tonsillectomy and adenoidectomy. Methods In this prospective, single-center, randomized, double-blind, controlled trial, a total of 103 children were randomly assigned to group A (n = 51, glycopyrrolate 0.005 mg/kg) or B (n = 52, atropine 0.01 mg/kg). The follow-up anesthetic induction and maintenance protocols were the same in both groups. Vital signs, duration of surgery, extubation time, degree of wetness around the vocal cords during tracheal intubation, weight of oral secretions, and perioperative complications were recorded. Results No significant differences were observed in the degree of wetness around the vocal cords during tracheal intubation, as well as in the weight of oral secretions, duration of surgery, or extubation time, between the two groups. The intraoperative and postoperative heart rates were lower in group A than in group B (110.18 ± 10.58 vs. 114.94 ± 11.14, p = 0.028; 96.96 ± 10.81 vs. 103.38 ± 10.09, p = 0.002). The differences observed in the intraoperative and preoperative heart rates were lower in group A than in group B (23.84 ± 9.62 vs. 29.65 ± 8.75, p = 0.002). The differences observed in the postoperative and preoperative heart rates were lower in group A than in group B (10.63 ± 9.97 vs. 18.09 ± 9.39, p = 0.000). Conclusion Glycopyrrolate showed a smoother change in heart rate than atropine during and after tonsillectomy and adenoidectomy, with no effect on BP or recovery quality, and did not increase oral secretions. The findings indicate that glycopyrrolate can serve as an alternative to atropine to prevent secretions in anesthesia induction for tonsillectomy and adenoidectomy in children. Trial registration: This study was registered with the Chinese Clinical Trial Registry (Registration Number: ChiCTR2200063578; Date of Registration: 12/09/2022).